STRUKTUR BERITA BERTEMA PENDIDIKAN KARAKTER DALAM MEDIA DARING KOMPAS.ID DAN TEMPO.CO - Emil Putri Nur Dewanti; Dian Hartati; Suntoko Suntoko (Universitas Batanghari, 2026)
This paper presents an analysis of the structure and themes of news articles in the online media platforms Kompas.id and Tempo.co. The aim of this study is to identify the news structures and themes found in character education news published in the January–May 2025 editions. The researcher applied a qualitative approach using a descriptive qualitative method. The subjects of this study were news articles from the online media Kompas.id and Tempo.co, while the object of the research was the structure of news articles themed on character education. The results indicate that the analysis of ten character education news articles in Kompas.id and Tempo.co shows that the news articles generally contain complete structural elements, consisting of: headline, dateline, lead, body, and closing. In Kompas.id, four news articles have complete structural elements, while one article lacks complete structure. In Tempo.co, three news articles have complete structural elements, while the other two lack complete structural elements. Both online media platforms present clear main topics supported by relevant subtopics.